2022
DOI: 10.14569/ijacsa.2022.0130303
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Rounding for Image Interpolation and Scan Conversion

Abstract: The stochastic rounding (SR) function is proposed to evaluate and demonstrate the effects of stochastically rounding row and column subscripts in image interpolation and scan conversion. The proposed SR function is based on a pseudorandom number, enabling the pseudorandom rounding up or down any non-integer row and column subscripts. Also, the SR function exceptionally enables rounding up any possible cases of subscript inputs that are inferior to a pseudorandom number. The algorithm of interest is the nearest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…First, it is important to remember that the nearest neighbor interpolation would be the simplest option to interpolate GT masks due to its inherent advantage of not creating non-original or extra class labels in the interpolated masks. The only problem is the deterministic rounding function on which its pixel selection strategy is based [48]. Such a strategy slightly shifts the entire image content to some extent, and is responsible for creating heavy jagged artefacts in interpolation results [35,45,48].…”
Section: A Novel Strategy For Removing Extra Class Labels In Interpol...mentioning
confidence: 99%
“…First, it is important to remember that the nearest neighbor interpolation would be the simplest option to interpolate GT masks due to its inherent advantage of not creating non-original or extra class labels in the interpolated masks. The only problem is the deterministic rounding function on which its pixel selection strategy is based [48]. Such a strategy slightly shifts the entire image content to some extent, and is responsible for creating heavy jagged artefacts in interpolation results [35,45,48].…”
Section: A Novel Strategy For Removing Extra Class Labels In Interpol...mentioning
confidence: 99%
“…In total, ~25,000 candidate SNPs for environmental associations were kept for the analysis. Finally, we used nearest‐neighbor interpolation (as in Rukundo & Cao, 2012: custom scripts available in the GitHub repository) to predict the RONA values for the entire distribution of the two species for spatial visualization.…”
Section: Methodsmentioning
confidence: 99%
“…sis. Finally, we used nearest-neighbor interpolation (as inRukundo & Cao, 2012: custom scripts available in the GitHub repository) to predict the RONA values for the entire distribution of the two species for spatial visualization.3 | RE SULTS3.1 | Populations exhibiting a high level of admixture are spread across three climatic groupsWe used the same sampling of 55 populations covering the whole range of P. abies and the western part of the distribution range of P. obovata as inZhou et al (2023). Using a combination of population genetics analyses, the authors showed that there are two main genetic entities: one western cluster, corresponding to Norway spruce (P. abies), centered on the Alps and the Carpathians, and extending toward Scandinavia and the Russian Plains, and one eastern cluster stemming from Siberia, east of the Urals Mountains and corresponding to what has generally been recognized as Siberian spruce (P. obovata).…”
mentioning
confidence: 99%
“…As shown in the Figure 2c, decrease in the width of the bar pattern is visible which is due to finite length of the tracks with an increase in the track density. The simulated images were scaled down to 188 pixels × 188 pixels using the nearest neighbor method 46 where size of one pixel is equivalent to 0.3 µm (typical diameter of a silver grain). Figures 2d, 2e and 2f show resized and inverted images of Figures 2a, 2b and 2c, respectively.…”
Section: A Estimation Of Track Densitymentioning
confidence: 99%